Firm-specific Factors, Foreign Market Heterogeneity, and Entry Mode Choice: an Examination of Haier’s Internationalization - Xu, Yixing (2012)
A lot of theories have been propounded has made great contribution to the enterprise internationalization and entry strategy. Since the 1990s enterprise from emerging markets have started at a great pace of expanding their business abroad. This has aroused worldwide speculation and tension. Due to the lack of assets including advanced technology, R&D facilities, talented human capital, managerial expertise, and natural resources, new MNEs were triggered to acquire these critical resources through international expansion. They differ sharply from MNEs from advanced developed markets, which generally leverage and exploit their ownership-specific competitive advantages in foreign countries. However, less attention has been paid to the internationalization of new MNEs and the firm-specific factors’ influence on firms’ entry mode choice. Furthermore, MNEs have been using various approaches in entering their target markets. For MNEs from emerging markets, institutional factors are considered as a very important determinant in their internationalization and entry mode choice, thus the choice of entry mode would also influenced by the host country-specific factors. This dissertation examined the internationalization of new MNEs and how the interaction between firm-specific factors and host country-specific factors influence the entry mode choice of new MNEs. By employing a case study of Haier Group, this study was aimed to gain deeper insight on new MNEs’ internationalization and how they enter into target markets. From the findings, it was revealed that, Haier had adopted exporting, joint venture, wholly owned subsidiaries and other strategic alliance during its internationalization process. In addition, it found that firm’s specific assets and capabilities and multinational experience are what restricted Haier’s entry mode choice of exporting and joint venture in its early stage of internationalization. Haier’s company objective and local market potential are the determinant factors that result Haier establish wholly owned subsidiaries in foreign markets, and the influence of local institutional environment on Haier’s entry mode choice is much heavier in markets at developing countries than developed countries.